A Reduction in Maximal Incremental Exercise Test Duration 48 h Post Downhill Run Is Associated with Muscle Damage Derived Exercise Induced Pain - Chrismas, Bryna C. R.; Taylor, Lee; Siegler, Jason C.; Midgley, Adrian W. (Frontiers in Physiology, 2017)
PURPOSE: To examine whether exercise induced muscle damage (EIMD) and muscle soreness reduce treadmill maximal incremental exercise (MIE) test duration, and true maximal physiological performance as a consequence of exercise induced pain (EIP) and perceived effort. METHODS: Fifty (14 female), apparently healthy participants randomly allocated into a control group (CON, n = 10), or experimental group (EXP, n = 40) visited the laboratory a total of six times: visit 1 (familiarisation), visit 2 (pre 1), visit 3 (pre 2), visit 4 (intervention), visit 5 (24 h post) and visit 6 (48 h post). Both groups performed identical testing during all visits, except during visit 4, where only EXP performed a 30 min downhill run and CON performed no exercise. During visits 2, 3 and 6 all participants performed MIE, and the following measurements were obtained: time to exhaustion (TTE), EIP, maximal oxygen consumption (V ̇O_(2max⁡)), rate of perceived exertion (RPE), maximum heart rate (HR_max ), maximum blood lactate (BLa_max) and the contribution of pain to terminating the MIE (assessed using a questionnaire). Additionally during visits 1, 2, 3, 5 and 6 the following markers of EIMD were obtained: muscle soreness, maximum voluntary contraction (MVC), voluntary activation (VA), creatine kinase (CK). RESULTS: There were no significant differences (p ≥ 0.32) between any trials for any of the measures obtained during MIE for CON. In EXP,TTE decreased by 34 s (3%), from pre 2 to 48 h post (p < 0.001). There was a significant association between group (EXP, CON) and termination of the MIE due to ‘pain’ during 48 h post (χ2 = 14.7, p = 0.002). CONCLUSION: EIMD resulted in premature termination of a MIE test (decreased TTE), which was associated with EIP, soreness, MVC and VA. The exact mechanisms responsible for this require further investigation.